Cardiovascular Magnetic Resonance Imaging’s Prognostic Utility in the Evaluation of Hypertrophic Cardiomyopathy Patients’ Long-Term Outcomes and Mortality: A Review - Farid, Muhammad Imran; Butt, Muhammad Meezan; Nasir, Abdul Wahab; Arshad, Muhammad Umar; Ramachandran, Vignesh; Shahzad, Muhammad Aliyan; Ahmad, Irshad (Indus Journal of Bioscience Research, 2025)
Background: As an additional imaging modality, cardiac magnetic resonance imaging (CMR) is valuable in the evaluation of patients with suspected or diagnosed hypertrophic cardiomyopathy (HCM). Objective: Aim was to determine the effectiveness of cardiac magnetic resonance imaging to diagnose long term outcomes among patients of hypertrophic cardiomayopathy. Given that HCM in children is linked to a higher risk of mortality and worse long-term outcomes, the prognosis and quality of life for these children are greatly affected by the age at which symptoms first appear and the underlying cause of their condition. It is crucial to correctly assess the heart and determine the HCM phenotype in order to make a diagnosis, stratify the prognosis, and do follow-up. The anatomy and function of the heart can be studied by cardiac magnetic resonance (CMR) scans, which can characterize tissues and evaluate blood flow and perfusion. Using CMR, minor anomalies in the myocardial composition can be detected and the various phenotypic expression of HCM can be characterized. The capacity to assess the severity and breadth of cardiac fibrosis using parametric mapping or late-gadolinium enhanced sequences is exclusive to CMR and is especially helpful for clinical assessment and prognostic stratification of children with HCM. Furthermore, HCM in children may worsen with time. Since the pace, timing, and severity of disease progression differ from patient to patient, it is crucial to closely monitor diagnosed patients’ hearts and do serial follow-up throughout their lifetimes. Focusing on its clinical function in diagnosis, prognosis, and serial follow-up, this review provides an updated overview of CMR’s usage in childhood HCM.